SEEMANN, Jörn (Org.). A Aventura Cartográfica: Perspectivas, Pesquisas e Reflexões sobre a Cartografia Humana. Fortaleza, Expressão Gráfica, 2005/2006, 224 p. - Santos, Clézio Santos (Sociedade & Natureza, 2008)
SEEMANN, Jörn (Org.). A Aventura Cartográfica: Perspectivas, Pesquisas e Reflexões sobre a Cartografia Humana. Fortaleza, Expressão Gráfica, 2005/2006, 224 p.